Compositions of seed fatty acids in some Vicia L. taxa from Turkey - Emre, Irfan; Sahin, Ahmet; Yilmaz, Okkes; Genc, Hasan; Bahsi, Muammer (Soc Botanique France, 2011)
In the present study, fatty acid composition in mature seeds of the Vicia L. taxa were determined by using gas chromatography. Present results indicate that the seed oils of studied Lathyrus taxa have palmitic acid (C16:0) and stearic acid (C18:0) as major saturated fatty acids. Moreover, the present data showe that oleic acid (C18:1), linoleic acid (018:2 n 6) and a-linolenic acid (C18:3 n 3) were major unsaturated fatty acids in studied taxa. The highest oleic acid (C18:1 n 9) content was found in V. crocea (Desf.) B. Fedstch. (26.5%) but it was found at the lowest level in V. mollis (7.8%). In addition, present study determine that investigated Vicia species have linoleic acid (46.4-791%) and linolenic acid (3.8-21.3%) contents.
Keywords: gas chromatography; saturated fatty acids; unsaturated fatty acids; Vicia